Influence of the technique and comorbidities in hypofractionated radiotherapy for prostate cancer - Correa Generoso, Raquel; Navarro, Inmaculada; Lobato, Mario; Otero, Ana; Jerez, Inmaculada; Rico, José Manuel; Zapata Martínez, Irene; Lupiáñez Pérez, Yolanda; Medina Carmona, José Antonio; Olmos, David; Gómez-Millán Barrachina, Jaime (Springer Link, 2020)
To analyze the differences in toxicity and biochemical relapse-free survival with hypofractionated radiotherapy with three-dimensional radiotherapy (3D-CRT) or volumetric arc therapy (VMAT) for prostate cancer taking into account comorbidity measured using the Charlson Comorbidity Index (CCI). Methods: From January 2011 to June 2016, 451 patients with prostate cancer were treated with 60 Gy (20 daily fractions). VMAT or 3D-CRT was used. Distribution by stage: 17% low-risk, 27.2% intermediate-risk; 39.2% high-risk, 16.6% very high-risk. Mean CCI was 3.4. Results: With a median follow up of 51 months, most patients did not experience any degree of acute GI toxicity (80.9%) compared to 19.1%, who experienced some degree, mainly G-I /II. In the multivariate analysis, only technique was associated with acute GI toxicity ≥ G2. Patients treated with VMAT had greater acute GI toxicity compared with those who received 3D-CRT (23.9% vs. 13.5%, p = 0.005). With respect to acute GU toxicity, 72.7% of patients experienced some degree, fundamentally G-I/II. Neither age, CCI, nor androgen deprivation therapy (ADT) were associated with greater toxicity. Overall survival at 2, 5 and 7 years was 97%, 88% and 83% respectively. The only factor with statistical significance was CCI, with a greater number of events in individuals with a CCI ≥ 4 (p < 0.03). Conclusions: Hypofractionated radiotherapy for prostate cancer is an effective, well-tolerated treatment even for elderly patients with no associated comorbidity. Longer follow up is needed in order to report data on late toxicity.
Keywords: Próstata - Cáncer; Charlson index;; Hipofractionation;; Image guided radiotherapy;; Prostate cancer;; VMAT.